External Minority Stress, Gender Dysphoria, and Capability for Suicide Among Transgender Adults: A Daily Diary Study - Botelho, Elliott (Journal of interpersonal violence, 2023)
This study analyzed whether external gender-related minority stress (i.e., discrimination, rejection, and violence) and gender dysphoria contribute to same-day and next-day acquired capability for suicide (ACS) in a sample of transgender adults residing in the southeastern United States. A sample of transgender participants (n = 38, 84.2% White, average age = 28.6 years) residing in the southeastern United States completed daily surveys on discrimination, rejection, violence, gender dysphoria, and ACS over 30 days (n = 836 of the 1,140 surveys sent out were completed). External minority stress (i.e., rejection, discrimination, and violence) was very common in this sample. External minority stress experiences were reported on 16% of the completed daily surveys, and 68% of the sample reported experiencing such stress at least once over the 30-day study period. Similarly, gender dysphoria occurred on 37.2% of the completed days and was experienced on at least 1 day by 78.9% of the participants over the 30-day survey period. Multilevel modeling showed daily experiences of discrimination and rejection, but not gender dysphoria, were positively associated with same-day ACS. Violence trended toward significance in correlating with same-day capability for suicide. Neither external minority stress nor gender dysphoria were associated with next-day ACS while controlling for acquired capability reported on the previous day. These preliminary data support proximal associations of external gender minority stress with same-day, but not next-day, ACS. Findings from this study advance understanding of how anti-transgender discrimination and violence contribute to increased capability for suicide in a population at increased risk for suicide.